Pb2Bi2GaB3O11, a new congruent-melting galloborate containing two types of asymmetric cations with a moderate birefringence. Issue 47 (16th November 2016) - Liu, Lili; Yang, Yun; Li, Linping; Yang, Zhihua; Pan, Shilie
Abstract : Pb2 Bi2 GaB3 O11 possesses a moderate birefringence of 0.07 at 589 nm originating from two stereoactive lone-pair cations and π-conjugated BO3 groups. Abstract : Pb2 Bi2 GaB3 O11, a new congruent-melting galloborate, which simultaneously contains two types of lone-pair cations and a π-conjugated system in one crystal structure, has been discovered through spontaneous crystallization. Single-crystal X-ray structural analysis shows that Pb2 Bi2 GaB3 O11 crystallizes in the monoclinic space group of C 2/ c . The parameters of the unit cell are a = 17.318(5) Å, b = 8.868(3) Å, c = 6.779(2) Å, β = 90.238(4)° and Z = 6. The structure of Pb2 Bi2 GaB3 O11 features three kinds of tunnels, circled by cation polyhedra, in two of which isolated BO3 groups reside. However, the open Bi4 O4 channel, as the third tunnel formed by the Bi–O polyhedra, is hollow. Pb2 Bi2 GaB3 O11 possesses an experimental band gap of 4.43 eV and an ultraviolet (UV) cut-off edge of about 280 nm, which is proven by its diffuse reflection spectrum. Theoretical calculations have also been executed to evaluate its band structure, partial density of state (PDOS) and birefringence. The results indicate that the title compound possesses a direct band gap with a theoretical value of 3.48 eV, and even indicate that the Pb 2+ and Bi 3+ ions are stereochemically active and cooperate with the BO3 groups, which contributes to a moderate birefringence of about 0.07 at 589 nm for Pb2 Bi2 GaB3 O11 .